Trend changes on raw materials markets - Heinz Kolbe (Intereconomics, 1988)
1987 saw a change in trends on many international raw materials markets. Prices, which had been under pressure for several years, began to rise again. This trend cannot be expected to continue everywhere in 1988, however.
Keywords: 330